La clé du futur : savoir analyser l’environnement - Duguay, Benoit (Assurances)

(untitled) (HEC Montréal, 1985)
This article emphasizes the necessity of closely monitoring environmental changes, in order to allow an organization's adaptation to prevailing external conditions. It is crucial for the very survival of a firm that such an analysis be performed because only then can managers take advantage of opportunities and/or avoid threats initiated by those modifications.